2018
DOI: 10.1002/celc.201800858
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Integrated Porous Leaf‐like CuO Nanoplate Array‐Based Anodes for High‐Performance Lithium‐Ion Batteries

Abstract: Developing high-energy-density lithium-ion batteries (LIBs) is of great significance for their wider commercialized application. The design of self-integrated electrodes can be treated as a valid approach to achieve this goal. In this work, a facile and low-cost wet chemical oxidation strategy is put forward to prepare self-integrated porous leaf-like CuO nanoplates on Cu foil substrates in situ. These nanoplates are then directly used as the anode for LIBs. The morphology, structure, and composition of the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“…The relatively high R total (117.53 Ω) and the low Li-ions diffusion coefficient (2.17 × 10 −13 cm 2 /s)of the CuO nanowires after cycling imply the low reversible capability of 385 mAh/g after 200 cycles shown in Figure 4. However, the CuO/Cu 2 O/Cu nanocomposites after cycling exhibit the lowest R cf (9.21 Ω), R ct (41.78 Ω), and R total (57.02 Ω), as well as the highest Li-ions diffusion coefficient (4.34 × 10 −12 cm 2 /s), indicating the higher electrochemical kinetics compared to the CuO nanowires, which are consistent with the outstanding electrochemical performance shown in Figures 4, 5 (Li et al, 2018;Hong et al, 2020;Liu et al, 2021). The outstanding electrochemical performance of the CuO/Cu 2 O/Cu nanocomposites could result from the unique nanocomposites structure and the synergetic effect of the components (Hu et al, 2013;Kim et al, 2016;Wang et al, 2020b;Murphin Kumar et al, 2020;Wang et al, 2021b;Li et al, 2021c).…”
Section: Electrochemical Performancesupporting
confidence: 78%
See 1 more Smart Citation
“…The relatively high R total (117.53 Ω) and the low Li-ions diffusion coefficient (2.17 × 10 −13 cm 2 /s)of the CuO nanowires after cycling imply the low reversible capability of 385 mAh/g after 200 cycles shown in Figure 4. However, the CuO/Cu 2 O/Cu nanocomposites after cycling exhibit the lowest R cf (9.21 Ω), R ct (41.78 Ω), and R total (57.02 Ω), as well as the highest Li-ions diffusion coefficient (4.34 × 10 −12 cm 2 /s), indicating the higher electrochemical kinetics compared to the CuO nanowires, which are consistent with the outstanding electrochemical performance shown in Figures 4, 5 (Li et al, 2018;Hong et al, 2020;Liu et al, 2021). The outstanding electrochemical performance of the CuO/Cu 2 O/Cu nanocomposites could result from the unique nanocomposites structure and the synergetic effect of the components (Hu et al, 2013;Kim et al, 2016;Wang et al, 2020b;Murphin Kumar et al, 2020;Wang et al, 2021b;Li et al, 2021c).…”
Section: Electrochemical Performancesupporting
confidence: 78%
“…The R cf , R ct , and the total resistance of R total for both CuO/Cu 2 O/Cu nanocomposites and CuO nanowires are much smaller after cycling, which indicates the increased electric conductivity due to the structure change and the formation of Cu component during the cycling process ( Li et al, 2018 ; Hong et al, 2020 ; Wang et al, 2020b ; Liu et al, 2021 ). The relatively high R total (117.53 Ω) and the low Li-ions diffusion coefficient (2.17 × 10 −13 cm 2 /s)of the CuO nanowires after cycling imply the low reversible capability of 385 mAh/g after 200 cycles shown in Figure 4 .…”
Section: Resultsmentioning
confidence: 99%
“…Obviously, the R s value of the electrode after cycling does not change too much compared to the one before cycling, while the R ct values increases slightly, due to the SEI formation. However, the value of Warburg impedance (σ w ) after 50 cycles is significantly reduced compared with the fresh state, indicating the diffusion of Li + will become faster in deep cycling, confirmed by the increased capacity after the initial cycles . Moreover, the relationship between real resistance (Z’) and total resistance (Z) is provided in Figure S6 (Supporting Information), confirming the slightly reduced total resistance after 50 cycles.…”
Section: Resultsmentioning
confidence: 63%
“…On the other hand, various CuO micro‐nanostructures and hybrids have been fabricated to enhance the structural stability and electrochemical performance for LIBs. In this respect, CuO/Cu hybrids, flower‐like/thorn‐like CuO/C microspheres, dandelion‐like nanocomposites, porous nanorods, pompon‐like hierarchical hollow microspheres, hollow octahedral, hollow nanospheres, porous nano‐labyrinths, Cu 1.5 Mn 1.5 O 4 nanoplates/hollow CuO, Mn 3 O 4 /CuO@TiO 2 submicroboxes, and yolk‐shell CuO@CuFe 2 O 4 composites have been reported. The unique nanostructure of the material can provide a continuous electron pathway and greatly shorten the distance for Li‐ion diffusion, which can effectively enhance the rate capability.…”
Section: Introductionmentioning
confidence: 99%
“…The lower the slope of Z' vs. ω À 1/2 , the faster the Li ions diffusion rate was. [52,53] It showed that the σ value of PMo 12 À SiO 2 @NÀ C electrode dropped sharply from 810 (before cycling) to 14 (after 1000 cycles) (Figure 5b). The σ value of SiO 2 @NÀ C electrode showed a similar trend, which dropped from the initial 136 to 21 after 1000 cycles (Figure S12).…”
Section: Resultsmentioning
confidence: 97%